Case reportTerbinafine-induced subacute cutaneous lupus erythematosus in two patients with systemic lupus erythematosus successfully treated with topical corticosteroids - Kalińska-Bienias, Agnieszka; Kowalewski, Cezary; Woźniak, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
So far in the literature there have been reported only 5 patients with a recognized and well-documented history of systemic lupus erythematosus (SLE) who developed SCLE after terbinafine introduction. Here we report two women suffering from SLE who developed SCLE after initiation of oral terbinafine for onychomycosis. Skin lesions in both of them were extensive, located on the trunk, and upper and lower extremities. No exacerbation of SLE symptoms was observed at that time. Despite severe skin lesions, patients revealed good response to topical corticosteroids within a few weeks. The systemic review of the literature and our experience on terbinafine-induced SCLE developing in patients with SLE allowed to create a description for this special subset: a) terbinafine-induced SCLE usually develop in 1–8 weeks after terbinafine introduction, b) skin lesions are usually severe, disseminated including lower extremities, c) patients present Ro/SS-A La/SS-B antibodies, but anti-histone antibodies are rarely observed, d) exacerbation of SLE symptoms is rather not observed, e) eruptions clear within 2–8 weeks, f) withdrawal of terbinafine and topical corticosteroids should be considered as a first-line therapy in these cases, g) terbinafine should be carefully used in patients suffering from SLE.